2021
DOI: 10.1073/pnas.2102092118
|View full text |Cite
|
Sign up to set email alerts
|

PilB from Streptococcus sanguinis is a bimodular type IV pilin with a direct role in adhesion

Abstract: Type IV pili (T4P) are functionally versatile filamentous nanomachines, nearly ubiquitous in prokaryotes. They are predominantly polymers of one major pilin but also contain minor pilins whose functions are often poorly defined and likely to be diverse. Here, we show that the minor pilin PilB from the T4P of Streptococcus sanguinis displays an unusual bimodular three-dimensional structure with a bulky von Willebrand factor A–like (vWA) module “grafted” onto a small pilin module via a short loop. Structural mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 66 publications
1
40
0
Order By: Relevance
“…vWA domains have been reported in TFP-associated proteins from other organisms. For example, the vWA domain of the major pilin in Streptococcus agalactiae is essential for adhesion ( 10 ), and the MIDAS motif in the vWA domain of the major pilin in Streptococcus sanguinis has recently been shown to be important in binding to eukaryotic cells ( 11 ). Like the vWF ( 12 ), the vWA domain of the P. aeruginosa PA14 PilY1 protein also has a high number of cysteine residues; 7 out of the 11 cysteines in PilY1 are in its vWA domain.…”
Section: Introductionmentioning
confidence: 99%
“…vWA domains have been reported in TFP-associated proteins from other organisms. For example, the vWA domain of the major pilin in Streptococcus agalactiae is essential for adhesion ( 10 ), and the MIDAS motif in the vWA domain of the major pilin in Streptococcus sanguinis has recently been shown to be important in binding to eukaryotic cells ( 11 ). Like the vWF ( 12 ), the vWA domain of the P. aeruginosa PA14 PilY1 protein also has a high number of cysteine residues; 7 out of the 11 cysteines in PilY1 are in its vWA domain.…”
Section: Introductionmentioning
confidence: 99%
“…This domain is, thus, responsible for the adhesion properties of S . sanguinis T4P [ 9 ]. It is possible that while PilY1.1 is required for binding to the exopolysaccharide fraction of the extracellular matrix, PilY1.3 binds to proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been recently shown that S . sanguinis evolved a similar modularity by grafting a lectin and a von Willebrand factor A domain at the C terminus of either of two minor pilins, PilC and PilB, respectively [ 9 ]. This shows that distantly related bacterial species evolved T4P that by different strategies can adapt their adhesion ability to the environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 residues (α1) that supports a globular head ( 4 ). However, larger minor pilins—displaying extra domains "grafted" onto a pilin moiety and hence defined as modular ( 6 )—are not uncommon, which partly explains the extreme functional versatility of T4F. Pilins are assembled in filaments at the CM ( 3 ) in two steps.…”
mentioning
confidence: 99%